Review of the 2002 Conditionality Guidelines - Feridhanusetyawan, Tubagus; Ramakrishnan, Uma.; Thomas, Alun.; Van der Willigen, Tessa (Washington, D.C. : International Monetary Fund, 2005)
This paper focuses on the fact that the 2004-2005 conditionality review expands to include a review of the application of the new Guidelines on Conditionality, adopted in 2002. These guidelines were the culmination of a comprehensive and far-reaching review of conditionality that aimed to enhance the effectiveness of IMF-supported programs. They represented the first revision of the IMF's conditionality guidelines since 1979, and were developed by the IMF after seeking input from civil society and public forums held in several countries. This review comes at an early stage of experience with the new guidelines, and further evidence will be needed before definite conclusions can be drawn. The ultimate test of conditionality is whether it contributes to better economic outcomes, including over the medium term, and these cannot yet be gauged. Moreover, although this review draws in part on case studies, no substitute exists for cross-country analysis for identifying broad trends, and at this stage such analysis is hampered by small sample sizes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Core Area; Fund-Supported Program; Misc Pubs; Misc; Staff Statement; Romania